Chinese EFL learners' misconceptions of noun countability and article use. (June 2020) - Liu, Yingying; Lu, Xiaofei
Abstract: This study examined the relationship between Chinese English as a foreign language (EFL) learners' misconceptions of noun countability and errors in their article use. We compared the patterns of article-noun combinations in two written corpora, one of first-language English writers and one of Chinese EFL learners, to identify errors of article use and the nouns associated with those errors. Based on the results of the comparative corpus analysis, we invited a group of Chinese EFL learners to complete a forced-choice task designed to elicit article use with 13 target nouns, and subsequently conducted one-on-one stimulated recall interviews with the learners to elicit explanations for their choices. Analyses of the learners' task performance and interviews revealed learner misconceptions of countability as the primary source of article errors, as well as several additional sources. These findings shed light on the role of knowledge of countability in accurate article use and have useful implications for EFL pedagogy.